Tailoring therapies to counter the divergent immune landscapes of breast cancer - Attalla, Sherif; Taifour, Tarek; Muller, William (Frontiers in Cell and Developmental Biology, 2023)
Breast cancer remains a significant clinical concern affecting millions of women worldwide. Immunotherapy is a rapidly growing drug class that has revolutionized cancer treatment but remains marginally successful in breast cancer. The success of immunotherapy is dependent on the baseline immune responses as well as removing the brakes off pre-existing anti-tumor immunity. In this review, we summarize the different types of immune microenvironment observed in breast cancer as well as provide approaches to target these different immune subtypes. Such approaches have demonstrated pre-clinical success and are currently under clinical evaluation. The impact of combination of these approaches with already approved chemotherapies and immunotherapies may improve patient outcome and survival.